COVID-19 lockdown and police misconduct: a match made in South Africa - Ott Hill, Eva (Policing during the COVID-19 pandemic, 2024)
During the COVID-19 pandemic, police officers across the world have been asked to enforce the new governmental rules and regulations, often with no special training or clear instructions. This created the conditions of high discretion and low guidance. This study examines how the police in South Africa (the South African Police Service [SAPS]), an agency with a history rife with examples of violations of citizens’ rights and police misconduct, has adjusted to these new conditions. The analysis is conducted cognizant of the broader South African context in which the SAPS operates. We analyze various forms of police misconduct as documented in 50 unique newspaper reports during the first year of the pandemic, when the most stringent measures were introduced. These articles, collected from some of the leading South African online portals, reveal that the police in South Africa participated in various forms of police misconduct - as severe as murder, assault, and corruption - while enforcing the lockdown regulations.